PESANTREN AND MULTICULTURAL SOCIETY: A Study on Muslim Scholar Behavior at Islamic Boarding School Bangkalan Madura - Shofiyullah Mz (Asia-Pacific Journal on Religion and Society, 2021)
This article describes the roles of three Madurese kyais in developing and disseminating the awareness of multiculturalism in their respective community. This role is functional as they have often been involved in solving social and cultural problems in their respective areas. The research this article presents was focused on their active roles in the District of Bangkalan, an area in the East Java province where a handful number of religious and ethnic minorities live together with the Muslim Madurese majority. Leading three different Islamic boarding schools, Kyai Haji (KH) Abdullah Schal, KH Abd Muhaimin Makky, and KH A Jazuli Nur often used their respective pesantren as a proxy to disseminate the understanding of cultural pluralism in society. In this phenomenological research, the author used observations and in-depth interviews with the key figures to understand how the kyais functioned in society, and together with the local government, to spread an understanding of the importance of cultural diversity and contribute to providing solutions to cultural problems.